Analysis of logistic outsourcing in a paper manufacturing multinational (Research, Society and Development, 2025)
The transportation logistics department plays a vital role in the supply chain, acting as a direct link between the company and its customers. Logistics outsourcing has become a consolidated strategy for increasing operational efficiency and maintaining competitiveness. However, this practice presents companies with challenges that must be carefully managed, such as ensuring the quality of the services provided and aligning the company’s strategic goals with the performance of outsourced logistics operators. The use of key performance indicators (KPIs) is essential for monitoring services, preventing delays, communication failures, and supply disruptions. Integration with other departments through ERP systems, as well as investment in technology, contributes to traceability and transparency. External factors, such as cost fluctuations and supplier dependency, require well-structured contracts and ongoing monitoring processes. This study presents an analysis of logistics outsourcing in a multinational paper company, using literature review, interviews with industry professionals, and historical data analysis. Ultimately, the aim is to understand how logistics outsourcing impacts the transportation sector and how it can serve as a strategic tool to enhance efficiency and ensure high-quality deliveries.